Subnational Public Financial Management : Institutions and Macroeconomic Considerations - Albino, Maria; Ahmad, Ehtisham; Singh, Raju. (Washington, D.C. : International Monetary Fund, 2005)
Transparent public financial management at the subnational level requires institutions and processes that mirror those needed at the central government level, in order to generate better accountability and competition among different subnational governments, critical elements in ensuring good governance and efficiency of decentralized administrations. Further subnational debt also has implications for overall macroeconomic stability that concerns the central government. The key components are identified, with a particular focus on subnational debt monitoring and management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet